The impact of the use of vehcle exercises (physical mentality) to develop the skill of positioning and attitudes of the rulers women football - Abdul Hussein, Mohammed; Ayed, Farah (Journal of Physical Education, 2015)
I took the game of football growing global attention for being one of the most popular games in the world and has seen increasingly sophisticated in recent years and was the rulers a significant role in this development, including the rulers of women and to keep pace with this development has to be the development of refereeing skills of the rulers of women and on this, the researcher examined the use of exercises (Mrkph_bdnah mentality) to develop the skill of concentration, attitude and included a sample search on (10) football referees women (second-class Baghdad governorate) and adopted a researcher on the two tests to develop the skill of concentration and attitudes then used statistical methods that fit this research and then present and discuss the results through a contagious curriculum for 10 weeks Contains the development of concentration and skill positions to judge women exercises and then gave the researcher the most important conclusions and recommendations that fit this study